Pengaruh Pemberian Pupuk NPK Mutiara Terhadap Perkecambahan Benih Ampupu (Eucalyptus urophylla S. T Blake) - Yoseph Paskalis Ahoinnai; Astin E. Mau; Norman P. L. B. Riwu Kaho; Yusratul Aini (Program Studi Kehutanan, Fakultas Pertanian, Universitas Nusa Cendana, 2026)
Ampupu (Eucalyptus urophylla S.T. Blake) is an indigenous tree species from Indonesia that can adapt to poor soils, rocky areas, and even swampy conditions. This study aimed to (1) examine the effect of NPK Mutiara fertilizer on the germination of Ampupu seeds, and (2) identify the optimal fertilizer dosage for seed germination. The experiment was conducted using a Completely Randomized Design (CRD) with one factor and six treatments: P0 (control, without fertilizer Mutiara), P1 (NPK fertilizer Mutiaradose of 2.5 g/tray), P2 (NPK fertilizer Mutiara of dose 5 g/tray), P3 (NPK fertilizer Mutiara of dose 7.5 g/tray), P4 (NPK fertilizer Mutiara of dose 10 g/tray), and P5 (NPK fertilizer Mutiara of dose 12.5 g/tray), each replicated three times. Data were analyzed using the Least Significant Difference (LSD) test at the 5% level. Results indicated that NPK Mutiara fertilizer significantly affected germination percentage, germination speed index, and germination value. Among the treatments, P4 (NPK fertilizer Mutiara of dose 10 g/tray) produced the best outcomes, showing a significant difference compared to other treatments in all observed variables.